Introduction to Pain Management for Third-Year Medical Students Team-Based Learning Module - Kiernan Smith (Association of American Medical Colleges, 2021)
Introduction A frequently encountered complaint in primary care, pain has a variety of causes and treatments. To reduce mortality, the Centers for Disease Control released guidelines on opioid prescribing in 2016. Taking those guidelines into account, this team-based learning (TBL) module for third-year medical students on their family medicine clinical clerkship serves as an introductory application for treatment of nociceptive and neuropathic pain. Methods Students accessed preparticipation reading material online 1 week before the session. After students had been arranged into groups for the 1-hour module, each student completed an individual readiness assessment test (iRAT). Next, each group completed the group readiness assessment test (gRAT) using Immediate Feedback-Assessment Technique cards to give its answers. To complete the more complex learning objectives, groups answered the multiple-choice team application (tAPP) questions. Results Over 2 years, this module was administered to more than 400 students. Average iRAT scores were approximately 80% and gRAT scores nearly 100%. Groups scored approximately 70% on the tAPP questions. Students rated the module on a 5-point Likert scale (1 = strongly disagree, 5 = strongly agree) and provided individual comments. The course always received a score of at least 4, as well as consistent positive feedback. Discussion The module can easily be embedded into a preexisting clinical clerkship didactic series. It can also serve as a platform on which to build additional TBL modules following a more longitudinal course and more in-depth skills development in pain management.